Work Condition and Predictors of Quality of Work Life of Information System Personnel - Rethinam, Guna Seelan; Ismail, Maimunah (2008)
Dynamic and continuous developments of Information and Communication Technology (ICT) have brought significant changes to work condition. This revolutionary work condition has created pressure and led to various work consequences at workplace. Therefore, it is essential to examine the Quality of Work Life (QWL) among the Information System (IS) personnel those who are heavily involved in ICT work environment. Data from a sample of 453 IS personnel employed in Malaysian ICT organizations were gathered via self-administered mail questionnaire and analyzed using SPSS. This study utilized Job Demand-Control-Support Model to examine the work condition. The results were discussed based on the four types of work condition namely, passive, active, low strain and high strain work conditions and their consequences for QWL. The results show IS personnel fall in the active quadrant that allows them to experience better QWL. Based on regression analysis, it was found that variables of work condition, namely job demand, job control and social support were significant predictors of QWL among IS personnel.